2010
DOI: 10.1093/nar/gkq846
|View full text |Cite
|
Sign up to set email alerts
|

A role for human Dicer in pre-RISC loading of siRNAs

Abstract: RNA interference is a powerful mechanism for sequence-specific inhibition of gene expression. It is widely known that small interfering RNAs (siRNAs) targeting the same region of a target-messenger RNA can have widely different efficacies. In efforts to better understand the siRNA features that influence knockdown efficiency, we analyzed siRNA interactions with a high-molecular weight complex in whole cell extracts prepared from two different cell lines. Using biochemical tools to study the nature of the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 68 publications
(101 reference statements)
3
52
0
1
Order By: Relevance
“…51 In contrast, the protein has been shown to directly bind small interfering (si)RNAs. [52][53][54] By electrophoresis mobility shift assay (EMSA), using a radiolabelled control siRNA and recombinant MBP or MBP-TRBP, we observed several low mobility bands, which indicates that TRBP binds to the siRNA either as a monomer or as a multimer ( Fig. 2A, left).…”
Section: Rre Binds To Trbpmentioning
confidence: 99%
“…51 In contrast, the protein has been shown to directly bind small interfering (si)RNAs. [52][53][54] By electrophoresis mobility shift assay (EMSA), using a radiolabelled control siRNA and recombinant MBP or MBP-TRBP, we observed several low mobility bands, which indicates that TRBP binds to the siRNA either as a monomer or as a multimer ( Fig. 2A, left).…”
Section: Rre Binds To Trbpmentioning
confidence: 99%
“…The sncRNA-duplex/AGO-2 complex is called pre-RISC (pre-RNA-induced silencing complex) and requires the removal of one of the strands of the RNA, the passenger strand, in order to become an active RISC complex [81,82] (Figure 1). The strand that remains in RISC is known as the guide strand.…”
Section: Ptgsmentioning
confidence: 99%
“…It was previously reported that, in mammalian cell lysate, siRNA duplexes form a complex containing Dicer and TRBP (therein referred to as complex D or pre-RLC), which can be separated on polyacrylamide native gel (Pellino et al 2005;Sakurai et al 2011). Indeed, we readily detected such a complex D with radiolabeled let-7 siRNA duplex in WT MEF lysate and Dicer1 À/À MEF lysate supplemented with rDICER1 ( Fig.…”
Section: In Vitro Assays For Asymmetric Risc Assembly In Mammalsmentioning
confidence: 99%
“…Native gel analysis, UV crosslinking, dicing, and target cleavage assays Methods were previously described in detail and were used with minor modifications (Haley et al 2003;Pellino et al 2005;Yoda et al 2010;Kawamata and Tomari 2011;Sakurai et al 2011). In sum, in vitro RISC assembly reactions typically contained 3 mL 403 reaction mix, 10 nM target RNA, 10 nM radiolabeled RNA duplex, 4 mL cell lysate, and 1 mL rDICER1 in 10 mL reaction mixture.…”
Section: Preparation Of Recombinant Dicer1mentioning
confidence: 99%
See 1 more Smart Citation